2020
DOI: 10.3126/jcmsn.v16i3.30530
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Gynecological Surgery in Bharatpur Hospital: An Experience from a Government Tertiary Care Center of Central Nepal

Abstract: Background: The aim of the study was to share the experience of laparoscopic gynecologic surgery in a government hospital outside Kathmandu valley Method: A descriptive  cross-sectional study was carried out in Bharatpur Hospital from 15 Dec, 2018 to 15 June, 2019. Fifty consecutive patients who underwent laparoscopic gynecological procedures were included in the study and analyzed demographics, indication, hospital stay and complications. Results: The mean age of the patients (n = 50) was 34.6 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…In our study, the commonly performed procedures were ovarian cystectomy, salpingectomy, and diagnostic laparoscopy in the age group 25-44 years. This is in agreement with other studies as most of the benign ovarian pathologies, ectopic and reproductive issues occur in this age group [14,16,17]. The moderate to complex procedures like ovarian cystectomy and TLH contributed to a longer operating time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the commonly performed procedures were ovarian cystectomy, salpingectomy, and diagnostic laparoscopy in the age group 25-44 years. This is in agreement with other studies as most of the benign ovarian pathologies, ectopic and reproductive issues occur in this age group [14,16,17]. The moderate to complex procedures like ovarian cystectomy and TLH contributed to a longer operating time.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the services in MIS are limited to simple diagnostic and therapeutic procedures. Studies from resource-limited countries reported similar findings in terms of indications and type of procedure performed as they initiated gynecological minimal invasive procedures [13][14][15]. In our study, the commonly performed procedures were ovarian cystectomy, salpingectomy, and diagnostic laparoscopy in the age group 25-44 years.…”
Section: Discussionsupporting
confidence: 70%